The dolerite dyke swarm of Mongo, Guéra Massif (Chad, Central Africa): Geological setting, petrography and geochemistry - (:unkn) unknown (My University, 2017)
Dolerite dykes are widespread in the Mongo area within the granitic Guéra Massif (Chad, Central Africa). Dykes are several hundred metres to several kilometres long, a metre to decametre thick, and vertical, crosscutting the Pan-African granitic basement rocks. They are controlled by major Pan-African NNE-SSW, NE-SW and ENE-WSW faults. Rocks constituting the dykes exhibit typical doleritic textures (i.e. intergranular, ophitic or subophitic). They are mainly composed of phenocrysts, microcrysts and microlites of clinopyroxene, amphibole, plagioclase, alkali feldspar and Fe-Ti oxides. Mongo dolerites are classified into two groups: Group 1 of basalt and trachybasalt and Group 2 of basaltic trachyandesite, which follow a trend with continental tholeiite affinities, and are differentiated through fractional crystallization. Trace element enrichment and REE contents show the high melting degree at shallow depths of enriched sub-continental lithospheric mantle, whose composition is intermediate between OIB and MORB, contaminated by small amounts of sediment during older subduction. Mongo dolerites are interpreted as imprints of either the final stage of stabilization of ancient continental crust, or the initiation of tectonic activity related to Pan-African mobile belts.
Keywords: African Research